Beyond Plague Pits: Using Genetics to Identify Responses to Plague in Medieval Cambridgeshire. (November 2021) - Cessford, Craig; Scheib, Christiana L.; Guellil, Meriam; Keller, Marcel; Alexander, Craig; Inskip, Sarah A.; Robb, John E.
Abstract : Ancient DNA from Yersinia pestis has been identified in skeletons at four urban burial grounds in Cambridge, England, and at a nearby rural cemetery. Dating to between ad 1349 and 1561, these represent individuals who died of plague during the second pandemic. Most come from normative individual burials, rather than mass graves. This pattern represents a major advance in archaeological knowledge, shifting focus away from a few exceptional discoveries of mass burials to what was normal practice in most medieval contexts. Detailed consideration of context allows the authors to identify a range of burial responses to the second pandemic within a single town and its hinterland. This permits the creation of a richer and more varied narrative than has previously been possible.